Paul Maenz Köln Ausstellungen 1988. - Paul Maenz, Köln (Köln : Paul Maenz, 1989)
Disler, Martin ; Rockenschaub, Gerwald ; Darboven, Hanne ; Barry, Robert ; Dahn, Walter ; Schuyff, Peter ; Scholte, Rob ; Woodrow, Bill ; Dokoupil, Jiri Georg ; Roehr, Peter ; Opie, Julian ; Feldmann, Hans-Peter ; Clemente, Francesco ; Salvo ; Toroni, Niele
Duits
boek